PS 08-60 CELL FREE PLASMA DNA IN MATERNAL PLASMA AS A PREDICTIVE MARKER FOR PREGNANCY ASSOCIATED COMPLICATIONS. (September 2016) - Misra, Deepika; Yadav, Sonali; Singh, Renu; Banerjee, Monisha
Abstract : Objective: The aim of the study is to quantitate amounts of plasma DNA (pDNA) and cell free fetal DNA (cffDNA) between healthy pregnancy and pregnancy associated complications such as pre-eclampsia (PE) and gestational diabetes mellitus (GDM) using SYBR Green I based assay in real-time quantitative PCR (qPCR). Design and Method: A total of 30 subjects were analyzed. pDNA from all samples was quantified spectrophotometrically and qPCR using β-actin and GAPDH housekeeping gene primers. cffDNA was quantified by qPCR of pDNA positive samples using Y-chromosome specific SRY primers. Statistics was applied using SPSS (ver. 21.0). Results: The qPCR analysis for housekeeping genes at II trimester of pregnancy demonstrated a significant increase ( P = 0.001) in concentration of pDNA in PE cases as compared with healthy pregnant subjects. Similarly, significant increase (< 0.005) was also observed in GDM cases at II trimester. The cffDNA concentration was significantly higher in GDM cases and showed some increase in PE cases as compared with healthy pregnant subjects. Conclusions: The study indicates that quantitative measurements of pDNA/cffDNA using qPCR may be used as screening markers for ascertaining pregnancy associated complications.